SYNERGIES IN THE RURAL DEVELOPMENT PROCESSES OF A COOPERATION PROJECT BETWEEN JAPAN AND COSTA RICA - Monge-Hernández, Carmen (2020)
Based on good practices developed by universities, public institutions and national and international organizations  that  work  on rural development in Costa Rica; it is   needed to understand and make visible the   faced challenges and achievements from the local participants perspective. The present exploratory qualitative research analyzes a rural development project carried out in the north of the country. From the capabilities approach for human development, the experience was carried out in, with and for the community. It   stands out for its transforming nature, for enhancing the expansion of individual and collective capacities in the communities and for proposing challenges for its sustainability.